ANALISIS INDEKS KEPUASAN PASIEN RAWAT INAP PADA PELAYANAN KESEHATAN DI RUMAH SAKIT BHAYANGKARA KENDARI TAHUN 2021 - Waode Marulana; Nasrul Nasrul; Asrip Putera (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
This research aims to explore the index of public satisfaction with inpatient services at Bhayangkara Kendari Hospital. This research design uses survey methods with explanatory research approach and data collection is carried out at once in one short study through questionnaires and in-depth interviews. The population in this study was all inpatients at Bhayangkara Kendari Hospital while the study took place. Determination of samples using accidental sampling method, so that the sample size is obtained as many as 100 respondents. The data analysis method used is the Community Satisfaction Index (IKM) referring to Permenpan RI Number 14 at 2017 and Importance-Performance Analysis.The results showed that the inpatient care index at Bhayangkara Kendari was 2.71 with a patient satisfaction index of 67.75 percent so that the overall quality and performance of inpatient services was “B (Good)". Furthermore, of the nine indicators of satisfaction index with   the level of conformity to aspects of public services at  Bhayangkara Kendari Hospital, showing  nineteen  aspects of service have satisfied inpatients,while the other seven  aspects are less satisfactory,  namely   openness of information about service requirements, service punctuality. officers (doctors / nurses), the communication ability of doctors in providing services, hospitality of service personnel, ease of service personnel encountered  in times of need, toilet cleanliness,  and availability of service support facilities.